Pengaturan Tindak Pidana Pemalsuan Uang dalam Perspektif Kepastian Hukum - Winata, Rendy; Lasmadi, Sahuri; Erwin (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study analyzes the regulation of the crime of counterfeiting from the perspective of legal certainty. Currently, the regulation is dualistic, with Law Number 7 of 2011 concerning Currency as the lex specialis and Law Number 1 of 2023 concerning the Criminal Code as the general provision. This dualism gives rise to various problems, such as unclear norms regarding the definitions of